A 3-D numerical modeling for prediction of mixed failure characteristics in composite single lap joints with hybrid adhesive layer. (October 2022) - Kim, Myong-Ho; Ri, Jun-Hyok; Hong, Hyon-Sik
Abstract: In general, the fracture of composite single lap joints (SLJ) may be induced by various combination of individual failure types such as adhesive and adherend failure. In this work, a 3-D numerical method is established in order to consider the mixed failure characteristics of the cohesive failure in adhesive layer, the delamination failure and the failure of fiber and matrix in composite adherend. A 3-D mixed-mode continuum damage model is applied for the simulation of cohesive failure in adhesive layer. The delamination failure is predicted by the cohesive zone model (CZM) at interlayer of plies adjacent to the adhesive layer, and orthotropic elastic model and Hashin criterion is used for the mechanical response of fiber and matrix. Some examples are considered in order to validate the current numerical method for composite SLJs with single and functionally graded adhesive layer. Also, these examples show the coupled failure characteristics details in the composite SLJs with various stacking sequences.